Quality of life in black African patients with keloid scars - Komenan Kassi; Kanga Kouame; Alexandre Kouassi; Ange Allou; Isidore Kouassi; Sarah Kourouma; Elidje Ecra; Abdoulaye Sangare (PAGEPress Publications, 2020)
A keloid scar is a benign skin tumor and we aimed to assess the Quality of Life (QoL) of black Africans with keloid scars based on the Dermatology Life Quality Index (DLQI). We conducted a cross-sectional descriptive study in the department of dermatology of the teaching hospital of Treichville in Ivory Coast. We recruited 132 patients with keloid and 3612 dermatoses without keloid: The prevalence was 3.50% (132/3753). We included 120 patients aged from 16 to 63 years old, the sex ratio was 0.46 (38/82) and the mean age was 34.20 years. Keloid scars were mostly secondary to skin trauma in 30.00 % and infection in 21.67%. The commonest site was the ear in 29.17 %. We reported Keloid with pain in 53.33% and pruritus in 95.00%. We observed psychological impact in 65.83%. The DLQI scores were moderate and high in 61.66 %. QoL was impacted significantly when keloid was associated with pain (p=0.046), pruritus (p=0.81) and functional disorders (p=0.29). The DLQI score could be a valuable tool to assess QoL in black African patients with keloid, for better treatment option.